2024
DOI: 10.1136/bmj-2023-078378
|View full text |Cite|
|
Sign up to set email alerts
|

TRIPOD+AI statement: updated guidance for reporting clinical prediction models that use regression or machine learning methods

Gary S Collins,
Karel G M Moons,
Paula Dhiman
et al.

Abstract: The TRIPOD (Transparent Reporting of a multivariable prediction model for Individual Prognosis Or Diagnosis) statement was published in 2015 to provide the minimum reporting recommendations for studies developing or evaluating the performance of a prediction model. Methodological advances in the field of prediction have since included the widespread use of artificial intelligence (AI) powered by machine learning methods to develop prediction models. An update to the TRIPOD statement is thus needed. TRIPOD+AI p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 97 publications
0
1
0
Order By: Relevance
“…This was a prognostic study, with the findings reported in alignment with the Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis + Artificial Intelligence (TRIPOD+AI) statement [ 27 ]. Specifically, PAD-specific prognostic biomarkers were identified from a pool of circulating myokines, and these biomarkers were used in combination with relevant clinical features to develop a predictive model for adverse limb events in patients with PAD.…”
Section: Methodsmentioning
confidence: 99%
“…This was a prognostic study, with the findings reported in alignment with the Transparent Reporting of a Multivariable Prediction Model for Individual Prognosis or Diagnosis + Artificial Intelligence (TRIPOD+AI) statement [ 27 ]. Specifically, PAD-specific prognostic biomarkers were identified from a pool of circulating myokines, and these biomarkers were used in combination with relevant clinical features to develop a predictive model for adverse limb events in patients with PAD.…”
Section: Methodsmentioning
confidence: 99%
“…Data analysis was performed using both Python (version 3.8.0) and R (version 4.2.2) programming languages. This study was carried out following the TRIPOD-AI guideline ( Supplemental Material 1 ) 27 . Saliency maps were generated to identify the areas of interest for the classifier across all test datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Reporting Quality Assessment: To assess the quality of the reporting, we decided to use TRIPOD+AI statement, which contains a comprehensive list of items that need to be reported for papers reporting development and/or validation of prognostic AI model [43]. List of sections and items on this list covers every key part of a manuscript including title, abstract, introduction, methods, results, and discussion.…”
Section: Methodologic Quality Assessmentmentioning
confidence: 99%